Plant biostimulants as natural alternatives to synthetic auxins in strawberry production: physiological and metabolic insights - Cardarelli, Mariateresa; El Chami, Antonio; Rouphael, Youssef; Ciriello, Michele; Bonini, Paolo; Erice, Gorka; Cirino, Veronica; Basile, Boris; Corrado, Giandomenico; Choi, Seunghyun; Kim, Hye-Ji; Colla, Giuseppe (Frontiers in Plant Science, 2024)
The demand for high-quality strawberries continues to grow, emphasizing the need for innovative agricultural practices to enhance both yield and fruit quality. In this context, the utilization of natural products, such as biostimulants, has emerged as a promising avenue for improving strawberry production while aligning with sustainable and eco-friendly agricultural approaches. This study explores the influence of a bacterial filtrate (BF), a vegetal-derived protein hydrolysate (PH), and a standard synthetic auxin (SA) on strawberry, investigating their effects on yield, fruit quality, mineral composition and metabolomics. Agronomic trials reveal that SA and BF significantly enhance early fruit yields due to their positive influence on flowering and fruit set, while PH treatment favors a gradual and prolonged fruit set, associated with an increased shoot biomass and sustained production. Fruit quality analysis shows that PH-treated fruits exhibit improved firmness and soluble solids content, whereas SA-treated fruits display lower firmness and soluble solids content. The ionomic analysis of leaves and fruits indicated that all treatments provide sufficient nutrients, with heavy metals within regulatory limits. Metabolomics indicates that PH stimulates primary metabolites, while SA and BF directly affect flavonoid and anthocyanin biosynthesis, and PH may enhance fruit quality through enhanced production of beneficial metabolites. This research offers valuable insights for optimizing strawberry production and fruit quality by harnessing the potential of natural biostimulants as viable alternative to synthetic compounds.